ANALISIS TINGKAT KENYAMANAN DI KABUPATEN INDRAGIRI HULU BERDASARKAN INDEKS THI (TEMPERATURE HUMIDITY INDEX) - Burhanudin Burhanudin (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
The rapid population growth in Indragiri Hulu Regency certainly has an impact in various sectors, the most obvious impact is the expert on land function to become a settlement. The increase in population will always be followed by the increase in residential buildings and non- settlements. This raises a variety of social and environmental problems. One of the obvious environmental problems is changes in air temperature and humidity. The increasing air temperature is something that can be felt immediately and affects the level of human comfort. In this study, the author will examine the level of comfort in Indragiri Hulu Regency using the Temperature Humidity Index (THI) method. The data used are data on air temperature and daily relative humidity in 1991 – 2020. The comfort level of Indragiri Hulu Regency represented by observation points at the Japura Meteorological Station in the data period 1991-2020 which was divided into 3 categories showed changes in the comfort level in Indragiri Hulu Regency in a period of 30 years. The presence of a reduction in the percentage of comfortable and partially comfortable categories. This was followed by an increase in the percentage of uncomfortable categories in the Indragiri Hulu Regency area. In addition, the trend of increasing THI on average per year over a period of 30 years shows an increase in the value of THI.